Active participles in Baltic - Kortlandt, Frederik (Baltistica, 2018)
The nom.pl. form of the active participles continues the original neuter sg. form, e.g. Lith. jái nuo dárbo rankàs suką̃. It is an impersonal predicative form to be compared with the Proto-Indo-European uninflected predicative form in *‑om that has been preserved in Old Prussian.